Is there a "dead-anyway" effect in willingness to pay for risk reduction? - Friedrich Breyer; Markus M. Grabka (Deutsches Institut für Wirtschaftsforschung (DIW), 2001)
In a recent paper, Pratt and Zeckhauser (JPE, 1996) discuss the measure of individuals' willingness to pay (WTP) for the reduction of risks to their lives which should be used for public decisions on risk-reducing projects. They suggest to correct observed WTP for the "dead-anyway" effect, which says that WTP increases with the level of risk to which the individual is exposed - an effect which is due to the imperfection of contingent-claims markets. We first discuss the theoretical foundations of the asserted effect and then propose a new empirical test based on the relationship between wealth, life satisfaction and exposure to risk of dying. Application of the test using two sets of survey data from Germany and Australia.yields no support for the asserted dead-anyway effect. – – In einem neueren Beitrag diskutieren Pratt and Zeckhauser (JPE, 1996), welches Maß der marginalen Zahlungsbereitschaft (WTP) von Individuen für die Reduktion ihrer Sterbewahrscheinlichkeit bei öffentlichen Entscheidungen über gefahrenerhebliche Projekte verwendet werden sollte. Sie schlagen vor, die gemessene WTP um den so genannten "Dead-anyway"-Effekt zu berichtigen, der besagt, dass die WTP mit dem Ausgangswert des Risikos zunimmt, dem das befragte Individuum ausgesetzt ist. Dieser Effekt beruht allerdings auf der Abwesenheit vollkommener Märkte für bedingte Güter. Wir diskutieren zunächst die theoretischen Grundlagen des "Dead-anyway"-Effekts und schlagen dann einen neuen empirischen Test mittels der Beziehung zwischen Vermögen, Sterberisiko und Lebenszufriedenheit vor. Eine Anwendung des Tests an Hand zweier Sätze von Umfragedaten aus Deutschland und Australien ergibt keine Bestätigung für den von Pratt und Zeckhauser behaupteten Effekt.
Keywords: J17; H43; 330; value of statistical life; mortality risk; contingent-claims markets; Willingness to pay; Risiko; Sterblichkeit; Vermoegen; Lebensqualitaet; Theorie; Deutschland; Australien; Lebenszufriedenheit